(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Natural hazards are "those aspects of the built elements that are dangerous to man and are caused by forces beyond his control." All atmospheric, hydrologic, and geophysical dangers are referred to as "natural hazards" in this study. When a danger overwhelms a susceptible population, a natural catastrophe occurs, resulting in widespread death and sickness. In the previous decade, over 300 natural disasters shook the world each year, affecting millions of workers and costing hundreds of billions of dollars. In the event of an accident, the catastrophe cycle offers a framework for coordinating a coordinated response, recovery, preventive, and anticipatory approach. Clean water, proper sanitation, food/nutrition, shelter, and the risk of bacterial infections are all factors to consider. Just a few of the challenges that might stymie recovery following a natural catastrophe. The many forms of environmental hazards and their consequences on individuals and the environment were covered in this article. Financial services in the aftermath of natural calamities, there was also some investigation. This study’s long-term objective is to give extensive and up-to-date information on environmental threats.